A binary glass-ceramic type sulfide oxide solid electrolyte and a preparation method and application thereof
Patent Information
- Application Number
- CN202611196639.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-07
- Publication Date
- 2026-10-16
AI Technical Summary
[0003]然而,传统硫化物固体电解质受限于原料高成本与工艺不稳定性,例如:常规锂源的原料为高纯Li2S,其化合物纯度与保质期均存在很大波动性,以其为原料制备的硫化物固体电解质存在以下缺陷:硫化物电解质材料在200℃即发生分解,且因含硫、磷组分极易起火燃烧,安全风险显著;因含有硫、磷阴离子,抗氧化能力弱,高电位下易氧化分解,难以适配高压体系,电化学窗口窄;硫化物电解质原料高纯且昂贵、合成条件苛刻、纯化难度大、良品率低,使材料成本为液态体系10倍以上,这些都极大的限制其产业化落地与推广
本发明提供一种二元玻璃陶瓷型硫氧化物固体电解质,包括以下结构通式所表示的物质:aLi2O-bP2S5,其中:65<a<75,25<b<35。本发明利用Li2O代替Li2S,制得的二元玻璃陶瓷型硫氧化物固体电解质,兼具实用离子电导率和成本优势,将该二元玻璃陶瓷型硫氧化物固体电解质用在电池中,同时表现出良好的化学稳定性和电学稳定性,具备良好的应用前景。
Smart Images

Figure CN122931013A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of solid electrolyte materials technology, and more specifically, to a binary glass-ceramic type sulfur oxide solid electrolyte, its preparation method, and its application. Background Technology
[0002] All-solid-state batteries using inorganic solid electrolyte materials are expected to break through the current bottlenecks in commercial lithium battery technology and guide the upgrading and innovation of energy storage devices and equipment due to their theoretical advantages of high safety, high specific energy, and (e)chemical stability. Currently, the main inorganic solid electrolytes can be divided into three categories: oxides, sulfides, and halides. Among them, sulfide solid electrolytes have attracted much attention due to their intrinsically high ionic conductivity.
[0003] However, traditional sulfide solid electrolytes are limited by the high cost of raw materials and the instability of the process. For example, the raw material for conventional lithium sources is high-purity Li2S, whose compound purity and shelf life are highly volatile. Sulfide solid electrolytes prepared from Li2S have the following drawbacks: sulfide electrolyte materials decompose at 200℃, and because they contain sulfur and phosphorus components, they are highly flammable, posing significant safety risks; due to the presence of sulfur and phosphorus anions, they have weak antioxidant capacity and are easily oxidized and decomposed at high potentials, making them difficult to adapt to high-voltage systems and resulting in a narrow electrochemical window; the raw materials for sulfide electrolytes are high-purity and expensive, the synthesis conditions are harsh, the purification is difficult, and the yield is low, making the material cost more than 10 times that of liquid systems. All of these factors greatly limit their industrialization and promotion. Summary of the Invention
[0004] The purpose of this invention is to provide a binary glass-ceramic type sulfur oxide solid electrolyte and its preparation method.
[0005] The technical problem solved by this invention is achieved by the following technical solution.
[0006] This invention provides a binary glass-ceramic type sulfur oxide solid electrolyte, comprising a substance represented by the following general structural formula: aLi2O-bP2S5, wherein: 65 < a < 75, 25 < b < 35.
[0007] The present invention provides a method for preparing the above-mentioned binary glass-ceramic sulfur oxide solid electrolyte, which includes: using Li2O and P2S5 as raw materials, heating within the molding temperature range of the sulfur oxide solid electrolyte material to obtain the binary glass-ceramic sulfur oxide solid electrolyte.
[0008] This invention provides an application of the above-mentioned binary glass-ceramic sulfur oxide solid electrolyte in a battery.
[0009] The present invention has the following beneficial effects: This invention provides a binary glass-ceramic type sulfur oxide solid electrolyte, comprising substances represented by the following general structural formula: aLi₂O-bP₂S₅, wherein: 65 < a < 75, 25 < b < 35. This invention utilizes Li₂O instead of Li₂S to prepare a binary glass-ceramic type sulfur oxide solid electrolyte, which combines practical ionic conductivity and cost advantages. When used in batteries, this binary glass-ceramic type sulfur oxide solid electrolyte exhibits good chemical and electrical stability, demonstrating promising application prospects. Attached Figure Description
[0010] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.
[0011] Figure 1(a) shows the X-ray diffraction pattern of the binary glass-ceramic sulfur oxide solid electrolyte 70Li2O-30P2S5 obtained in Example 1. Figure 1(b) shows the EIS impedance spectrum of the binary glass-ceramic sulfur oxide solid electrolyte 70Li2O-30P2S5 obtained in Example 1. Figure 2 The EIS impedance spectrum of the binary glass-ceramic sulfur oxide solid electrolyte 70Li2O-30P2S5 obtained in Example 2 is shown. Figure 3 The EIS impedance spectrum of the binary glass-ceramic sulfur oxide solid electrolyte 70Li2O-30P2S5 obtained in Example 3 is shown. Figure 4 The EIS impedance spectrum of the binary glass-ceramic sulfur oxide solid electrolyte 70Li2O-30P2S5 obtained in Example 4 is shown. Figure 5 The EIS impedance spectrum of the binary glass-ceramic sulfur oxide solid electrolyte 70Li2O-30P2S5 obtained in Example 5 is shown. Figure 6 EIS impedance spectrum of binary glass-ceramic sulfur oxide solid electrolyte 75Li2O-30P2S5 obtained in Comparative Example 1. Figure 7 The EIS impedance spectrum of the binary glass-ceramic sulfur oxide solid electrolyte 70Li2O-35P2S5 obtained in Comparative Example 2 is shown. Detailed Implementation
[0012] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.
[0013] The following is a detailed description of a binary glass-ceramic type sulfur oxide solid electrolyte and its preparation method provided by the present invention.
[0014] In a first aspect, the present invention provides a binary glass-ceramic type sulfur oxide solid electrolyte, comprising a substance represented by the following general structural formula: aLi2O-bP2S5, wherein: 65<a<75, 25<b<35.
[0015] As solid electrolytes used in all-solid-state batteries, sulfide solid electrolytes with high Li-ion conductivity are known. These sulfide solid electrolytes include Li₂S-P₂S₅ electrolytes, Li₂S-P₂S₅-LiBr-LiI electrolytes (with LiBr and LiI added), and Li₂S-P₂S₅ glass-ceramics and Li₂S-P₂S₅-LiBr-LiI glass-ceramics, which are glass-ceramicized from these electrolytes. However, these sulfide electrolytes, using conventional high-purity Li₂S as the lithium source, exhibit significant fluctuations in compound purity and shelf life. This results in traditional sulfide solid electrolytes being limited by high raw material costs and process instability, severely restricting their industrialization and widespread adoption.
[0016] To overcome the aforementioned problems in the existing technology, this invention provides a binary glass-ceramic type sulfur oxide solid electrolyte, comprising substances represented by the following general structural formula: aLi₂O-bP₂S₅, where: 65 < a < 75, 25 < b < 35. This invention uses Li₂O instead of Li₂S to prepare the binary glass-ceramic type sulfur oxide solid electrolyte, which makes the raw materials readily available and simplifies the preparation process. This effectively reduces the production cost of the electrolyte, improves the stability of the production process, and achieves the ionic conductivity required for industrial application. It achieves a balance between cost, safety, and practical ionic conductivity, demonstrating promising prospects for industrial application.
[0017] In some alternative implementations, the values of a and b are as follows: 68 < a < 72, 28 < b < 32.
[0018] Secondly, the present invention provides a method for preparing the above-mentioned binary glass-ceramic sulfur oxide solid electrolyte, which includes: using Li2O and P2S5 as raw materials, heating within the molding temperature range of the sulfur oxide solid electrolyte material to obtain the binary glass-ceramic sulfur oxide solid electrolyte.
[0019] In some optional embodiments, the method includes the following steps: mixing and ball milling Li2O and P2S5 to obtain precursor powder, and then annealing the precursor powder to obtain a binary glass-ceramic type sulfur oxide solid electrolyte.
[0020] In some optional embodiments, the mixed ball milling includes primary ball milling and secondary ball milling, wherein: the ball-to-material ratio of the primary ball milling and the secondary ball milling is 5-50:1, the rotation speed is 100-600 rpm, and the time is 0.2-60 hrs; preferably, the ball-to-material ratio of the primary ball milling to the secondary ball milling is 10-25:1, more preferably, the ball-to-material ratio of the primary ball milling to the secondary ball milling is 18-21:1; preferably, the rotation speed of the primary ball milling and the secondary ball milling is 120-550 rpm, more preferably, the rotation speed of the primary ball milling and the secondary ball milling is 145-505 rpm; preferably, the time of the primary ball milling and the secondary ball milling is 0.5-40 hrs, more preferably, the time of the primary ball milling and the secondary ball milling is 1-20 hrs.
[0021] In this invention, ball milling of the material results in a binary glass-ceramic sulfur oxide solid electrolyte exhibiting practical ionic conductivity and lower interfacial impedance after subsequent sintering. If the ball milling process is not performed within the aforementioned limits, it is difficult to obtain a target product with both high purity and high density using the ball-milled product.
[0022] In some optional embodiments, the annealing treatment is performed at a temperature of 150-300°C for 0.1-5 hrs, with a heating / cooling rate of 1-10°C / min; preferably, the annealing treatment is performed at a temperature of 180-280°C for 0.2-2 hrs, with a heating / cooling rate of 2-10°C / min; more preferably, the annealing treatment is performed at a temperature of 200-270°C for 0.3-1.5 hrs, with a heating / cooling rate of 5-8°C / min.
[0023] In some alternative embodiments, the annealing process is a programmed annealing process, which includes a preheating stage annealing process and a forming stage annealing process; Preferably, the annealing temperature in the preheating stage is 150-200℃, the annealing temperature in the forming stage is 200-300℃, the total time for the annealing in the preheating stage and the annealing in the forming stage is 0.1-5hrs, and the heating rate and cooling rate are both 1-10℃ / min.
[0024] Preferably, the programmed annealing process is carried out under a protective atmosphere, which includes one of helium (He), neon (Ne), argon (Ar), and nitrogen (N2); the flow rate of the protective gas in the programmed annealing process is controlled at 0-2 L / min. Preferably, the protective atmosphere conditions for the programmed annealing process mainly include one or more high-purity gases selected from argon (Ar) and nitrogen (N2); the flow rate of the protective gas in the programmed annealing process is controlled at 0.05-1 L / min. More preferably, the protective atmosphere conditions for the programmed annealing process include high-purity helium (He); the flow rate of the protective gas in the programmed annealing process is controlled at 0.1-0.5 L / min.
[0025] As can be seen from the above, the preparation method of the binary glass-ceramic sulfur oxide solid electrolyte provided by this invention replaces the existing Li2S with Li2O, a raw material with a reliable supply chain and significant cost advantages. This method offers advantages such as simple synthesis process, ease of industrial scale-up, and high cost-effectiveness of raw materials. The prepared binary glass-ceramic sulfur oxide solid electrolyte exhibits good electrochemical stability when used in all-solid-state batteries, making it a promising solid electrolyte option for practical application.
[0026] Thirdly, the present invention provides an application of the above-mentioned binary glass-ceramic sulfur oxide solid electrolyte in a battery.
[0027] The present invention will be further described below with reference to embodiments.
[0028] Example 1 The preparation method of the binary glass-ceramic type sulfur oxide solid electrolyte 70Li2O-30P2S5 is as follows: In an argon-filled glove box (water content ≤0.1ppm, oxygen content ≤0.1ppm), weigh Li2O and P2S5 according to the stoichiometric ratio, transfer them to a zirconia ball milling jar, fill with zirconia grinding beads at a ball-to-material ratio of 20:1, with a diameter of 3-12mm, and seal the ball milling jar.
[0029] Under an argon protective atmosphere, the process was carried out using a high-energy ball mill (German Pulverisette 7). A first ball milling was performed at 150 rpm for 1 hour, followed by a cleaning of the milled material. A second ball milling was performed at 500 rpm for 20 hours. The resulting precursor powder was then collected and pressed into tablets using molds.
[0030] The sheet-like precursor was subjected to programmed annealing in a vented tubular furnace or a muffle furnace under atmosphere protection. The annealing temperature during the preheating stage was 210℃, and the annealing time was 0.5hr; the annealing temperature during the shaping stage was 260℃, and the annealing time was 1hr; it was then cooled to room temperature, with a heating rate of 5℃ / min, a cooling rate of 5℃ / min, and a high-purity argon gas flow rate of 0.4L / min.
[0031] The harvested material was then ground and refined to obtain a binary glass-ceramic sulfur oxide solid electrolyte, 70Li2O-30P2S5, suitable for all-solid-state batteries. As shown in Figure 1(a), this material did not produce obvious characteristic diffraction peak intensities, exhibiting clear glass-ceramic characteristics. As shown in Figure 1(b), the EIS impedance curve measured using 150 mg of this material at 350 MPa shows that it has an ionic conductivity of 0.76 mS / cm and also exhibits good densification properties.
[0032] Example 2 The preparation method of the binary glass-ceramic type sulfur oxide solid electrolyte 70Li2O-30P2S5 is as follows: In an argon-filled glove box (water content ≤0.1ppm, oxygen content ≤0.1ppm), weigh Li2O and P2S5 according to the stoichiometric ratio, transfer them to a zirconia ball milling jar, fill with zirconia grinding beads at a ball-to-material ratio of 20:1, with a diameter of 3-12mm, and seal the ball milling jar.
[0033] Under an argon protective atmosphere, the process was carried out using a high-energy ball mill (German Pulverisette 7). A first ball milling was performed at 150 rpm for 1 hour, followed by a cleaning of the milled material. A second ball milling was performed at 500 rpm for 20 hours. The resulting precursor powder was then collected and pressed into tablets using molds.
[0034] The sheet-like precursor was subjected to programmed annealing in a vented tubular furnace or a muffle furnace under atmosphere protection. The annealing temperature during the preheating stage was 190℃, and the annealing time was 0.75hr; the annealing temperature during the shaping stage was 280℃, and the annealing time was 1.5hr; after which it was cooled to room temperature, with a heating rate of 5℃ / min, a cooling rate of 8℃ / min, and a high-purity argon gas flow rate of 0.4L / min.
[0035] The harvested material was then ground and refined to obtain a binary glass-ceramic sulfur oxide solid electrolyte, 70Li2O-30P2S5, which can be used in all-solid-state batteries. Figure 2As shown, the EIS impedance curve measured using 150 mg of this material at 350 MPa shows that it has an ionic conductivity of 0.56 mS / cm and also exhibits good densification properties.
[0036] Example 3 The preparation method of the binary glass-ceramic type sulfur oxide solid electrolyte 70Li2O-30P2S5 is as follows: In an argon-filled glove box (water content ≤0.1ppm, oxygen content ≤0.1ppm), weigh Li2O and P2S5 according to the stoichiometric ratio, transfer them to a zirconia ball milling jar, fill with zirconia grinding beads at a ball-to-material ratio of 20:1, with a diameter of 3-12mm, and seal the ball milling jar.
[0037] Under an argon protective atmosphere, the process was carried out using a high-energy ball mill (German Pulverisette 7). A first ball milling was performed at 150 rpm for 1 hour, followed by a cleaning of the milled material. A second ball milling was performed at 500 rpm for 20 hours. The resulting precursor powder was then collected and pressed into tablets using molds.
[0038] The sheet-like precursor was subjected to programmed annealing in a vented tubular furnace or a muffle furnace under atmosphere protection. The annealing temperature during the preheating stage was 200℃, and the annealing time was 0.25hr; the annealing temperature during the shaping stage was 270℃, and the annealing time was 0.5hr; after which it was cooled to room temperature, with a heating rate of 5℃ / min, a cooling rate of 2℃ / min, and a high-purity argon gas flow rate of 0.4L / min.
[0039] The harvested material was then ground and refined to obtain a binary glass-ceramic sulfur oxide solid electrolyte, 70Li2O-30P2S5, which can be used in all-solid-state batteries. Figure 3 As shown, the EIS impedance curve obtained using 150 mg of this material at 350 MPa shows that it has an ionic conductivity of 0.59 mS / cm and also exhibits good densification properties.
[0040] Example 4 A sulfur oxide solid electrolyte with an amorphous structure and its preparation method are described below. The general structural formula of this electrolyte material is 70Li2O-30P2S5. In an argon-filled glove box (water content ≤0.1ppm, oxygen content ≤0.1ppm), calculate the required mass of raw materials according to the stoichiometric ratio of the target structural formula. Weigh Li2O and P2S5 separately and transfer them to a zirconia ball mill jar. Fill the jar with zirconia grinding beads at a ball-to-material ratio of 20:1. The diameter of the grinding beads ranges from 3 to 12 mm. Seal the jar.
[0041] Under an argon protective atmosphere, the process was carried out using a high-energy ball mill (German Pulverisette 7). Pre-milling was performed at 150 rpm for 1 hour, followed by a primary ball milling at 500 rpm for 10 hours. The material adhering to the walls of the ball mill jar was then transferred to a glove box to remove it to the bottom. After sealing, the ball mill jar was transferred to the high-energy ball mill for a secondary ball milling at 500 rpm for 10 hours. The initially obtained precursor powder was then collected and pressed into tablets using a mold.
[0042] The sheet-like precursor was subjected to programmed sintering heat treatment in a ventilated tubular furnace or a muffle furnace under atmosphere protection. The first sintering nucleation temperature was 210℃, and the annealing time was 0.58hr; the second sintering nucleation temperature was 260℃, and the annealing time was 1.17hr; after which it was cooled to room temperature, with a heating rate of 2℃ / min, a cooling rate of 2℃ / min, and a high-purity argon gas flow rate of 0.5L / min.
[0043] The harvested material was then ground and refined to obtain an amorphous sulfur oxide solid electrolyte, 70Li₂O-30P₂S₅, suitable for all-solid-state batteries. Figure 4 As shown, the EIS impedance curve obtained using 200 mg of this material at 350 MPa shows that it has an ionic conductivity of 0.78 mS / cm.
[0044] Example 5 A sulfur oxide solid electrolyte with an amorphous structure and its preparation method are described below. The general structural formula of this electrolyte material is 70Li2O-30P2S5. In an argon-filled glove box (water content ≤ 0.1 ppm, oxygen content ≤ 0.1 ppm), calculate the required mass of raw materials based on the stoichiometric ratio of the target structural formula. Weigh 100% Li2O and 50% P2S5 respectively and transfer them to a zirconia ball mill jar. Fill the jar with zirconia grinding beads at a ball-to-material ratio of 20:1. The diameter of the grinding beads ranges from 3 to 12 mm. Seal the jar.
[0045] Under an argon protective atmosphere, the process was carried out using a high-energy ball mill (German Pulverisette 7). Pre-milling was performed at 150 rpm for 1 hour, followed by a primary ball milling at 500 rpm for 10 hours. The material adhering to the walls of the ball mill jar was then transferred to a glove box to remove the remaining material to the bottom. The remaining 50% of P2S5 was weighed and transferred to the ball mill jar. After sealing, the ball mill jar was transferred to the high-energy ball mill for a secondary ball milling at 500 rpm for 10 hours. The initially obtained precursor powder was then collected and pressed into tablets using a mold.
[0046] The sheet-like precursor was subjected to programmed sintering heat treatment in a ventilated tubular furnace or a muffle furnace under atmosphere protection. The first sintering nucleation temperature was 210℃, and the annealing time was 0.5hr; the second sintering nucleation temperature was 260℃, and the annealing time was 1hr; then it was cooled to room temperature, with a heating rate of 2℃ / min, a cooling rate of 2℃ / min, and a high-purity argon gas flow rate of 0.5L / min.
[0047] The harvested material was then ground and refined to obtain an amorphous sulfur oxide solid electrolyte, 70Li₂O-30P₂S₅, suitable for all-solid-state batteries. Figure 5 As shown, the EIS impedance curve obtained using 200 mg of this material at 350 MPa shows that it has an ionic conductivity of 0.97 mS / cm.
[0048] Comparative Example 1 The preparation method of the binary glass-ceramic type sulfur oxide solid electrolyte 75Li2O-30P2S5 is as follows: In an argon-filled glove box (water content ≤0.1ppm, oxygen content ≤0.1ppm), weigh Li2O and P2S5 according to the stoichiometric ratio, transfer them to a zirconia ball milling jar, fill with zirconia grinding beads at a ball-to-material ratio of 20:1, with a diameter of 3-12mm, and seal the ball milling jar.
[0049] Under an argon protective atmosphere, the process was carried out using a high-energy ball mill (German Pulverisette 7). A first ball milling was performed at 150 rpm for 1 hour, followed by a cleaning of the milled material. A second ball milling was performed at 500 rpm for 20 hours. The resulting precursor powder was then collected and pressed into tablets using molds.
[0050] The sheet-like precursor was subjected to programmed annealing in a vented tubular furnace or a muffle furnace under atmosphere protection. The annealing temperature during the preheating stage was 210℃, and the annealing time was 0.5hr; the annealing temperature during the shaping stage was 260℃, and the annealing time was 1hr; it was then cooled to room temperature, with a heating rate of 5℃ / min, a cooling rate of 5℃ / min, and a high-purity argon gas flow rate of 0.4L / min.
[0051] The harvested material was then ground and refined to obtain a binary glass-ceramic sulfur oxide solid electrolyte, 75Li₂O-30P₂S₅, suitable for all-solid-state batteries. Figure 6 As shown, the EIS impedance curve measured using 100 mg of this material at 350 MPa shows that it has an ionic conductivity of 0.18 mS / cm and also exhibits good densification properties.
[0052] Comparative Example 2 The preparation method of the binary glass-ceramic type sulfur oxide solid electrolyte 70Li2O-35P2S5 is as follows: In an argon-filled glove box (water content ≤0.1ppm, oxygen content ≤0.1ppm), weigh Li2O and P2S5 according to the stoichiometric ratio, transfer them to a zirconia ball milling jar, fill with zirconia grinding beads at a ball-to-material ratio of 20:1, with a diameter of 3-12mm, and seal the ball milling jar.
[0053] Under an argon protective atmosphere, the process was carried out using a high-energy ball mill (German Pulverisette 7). A first ball milling was performed at 150 rpm for 1 hour, followed by a cleaning of the milled material. A second ball milling was performed at 500 rpm for 20 hours. The resulting precursor powder was then collected and pressed into tablets using molds.
[0054] The sheet-like precursor was subjected to programmed annealing in a vented tubular furnace or a muffle furnace under atmosphere protection. The annealing temperature during the preheating stage was 210℃, and the annealing time was 0.5hr; the annealing temperature during the shaping stage was 260℃, and the annealing time was 1hr; it was then cooled to room temperature, with a heating rate of 5℃ / min, a cooling rate of 5℃ / min, and a high-purity argon gas flow rate of 0.4L / min.
[0055] The harvested material was then ground and refined to obtain a binary glass-ceramic sulfur oxide solid electrolyte, 70Li₂O-35P₂S₅, suitable for all-solid-state batteries. For example... Figure 7 As shown, the EIS impedance curve obtained using 100 mg of this material at 350 MPa shows that it has an ionic conductivity of 0.14 mS / cm and also exhibits good densification properties.
[0056] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A binary glass-ceramic type sulfur oxide solid electrolyte, characterized in that, This includes substances represented by the following general structural formula: aLi₂O-bP₂S₅, where: 65 < a < 75, 25 < b < 35.
2. The binary glass-ceramic type sulfur oxide solid electrolyte according to claim 1, characterized in that, The values of a and b are as follows: 68 < a < 72, 28 < b < 32.
3. The binary glass-ceramic type sulfur oxide solid electrolyte according to claim 1, characterized in that, The binary glass-ceramic type sulfur oxide solid electrolyte has an ionic conductivity greater than 0.56 mS / cm.
4. A method for preparing a binary glass-ceramic type sulfur oxide solid electrolyte according to any one of claims 1-3, characterized in that, It includes: using Li2O and P2S5 as raw materials, heating them within the molding temperature range of sulfur oxide solid electrolyte materials to obtain a binary glass-ceramic type sulfur oxide solid electrolyte.
5. The preparation method according to claim 4, characterized in that, Includes the following steps: Li2O and P2S5 were mixed and ball-milled to obtain precursor powder, which was then annealed and cooled to obtain a binary glass-ceramic type sulfur oxide solid electrolyte.
6. The preparation method according to claim 5, characterized in that, The mixed ball milling includes primary ball milling and secondary ball milling, wherein the ball-to-material ratio of primary ball milling and secondary ball milling is 5-50:1, the rotation speed is 100-600 rpm, and the time is 0.2-60 hrs. Preferably, the ball-to-material ratio of the primary ball milling to the secondary ball milling is 10-25:1; more preferably, the ball-to-material ratio of the primary ball milling to the secondary ball milling is 18-21:
1. Preferably, the rotation speed of the primary ball milling to the secondary ball milling is 120-550 rpm; more preferably, the rotation speed of the primary ball milling to the secondary ball milling is 145-505 rpm. Preferably, the time for the primary ball milling to the secondary ball milling is 0.5-40 hrs; more preferably, the time for the primary ball milling to the secondary ball milling is 1-20 hrs.
7. The preparation method according to claim 5, characterized in that, The annealing treatment is performed at a temperature of 150-300℃ for 0.1-5 hrs with a heating / cooling rate of 1-10℃ / min; preferably, the annealing treatment is performed at a temperature of 180-280℃ for 0.2-2 hrs with a heating / cooling rate of 2-10℃ / min; more preferably, the annealing treatment is performed at a temperature of 200-270℃ for 0.3-1.5 hrs with a heating / cooling rate of 5-8℃ / min.
8. The preparation method according to claim 7, characterized in that, The annealing process is a programmed annealing process, which includes a preheating stage annealing process and a forming stage annealing process. Preferably, the annealing temperature in the preheating stage is 150-200℃, the annealing temperature in the forming stage is 200-300℃, the total time for the annealing in the preheating stage and the annealing in the forming stage is 0.1-5hrs, and the heating rate and cooling rate are both 1-10℃ / min.
9. The preparation method according to claim 8, characterized in that, The programmed annealing process is carried out under a protective atmosphere, which includes one of helium (He), neon (Ne), argon (Ar), and nitrogen (N2); the flow rate of the protective gas in the programmed annealing process is controlled at 0-2 L / min.
10. The application of the binary glass-ceramic type sulfur oxide solid electrolyte according to any one of claims 1-3 or the binary glass-ceramic type sulfur oxide solid electrolyte prepared by the preparation method according to any one of claims 4-9 in a battery.